2017
DOI: 10.4014/jmb.1705.05081
|View full text |Cite
|
Sign up to set email alerts
|

Specific Expression of Interferon-�� Induced by Synergistic Activation Mediator-Derived Systems Activates Innate Immunity and Inhibits Tumorigenesis

Abstract: The synergistic activation mediator (SAM) system can robustly activate endogenous gene expression by a single-guide RNA. This transcriptional modulation has been shown to enhance gene promoter activity and leads to epigenetic changes. Human interferon-γ is a common natural glycoprotein involved in antiviral effects and inhibition of cancer cell growth. Large quantities of high-purity interferon-γ are important for medical research and clinical therapy. To investigate the possibility of employing the SAM system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…As expected, the increased tumor immunogenicity via dCas9-mediated transcriptional activation of pro-immunogenic genes increased CD4 + and CD8 + T cell infiltration into the tumor, thereby improving anti-tumor immunity. The findings were also supported by Liu et al.’s 130 earlier work from 2017, where HeLa cells edited using the same dCas9-SAM system to overexpress the IFNγ gene exhibited enhanced apoptosis, inhibited proliferation, and overall reduced tumor volume when implanted in immunodeficient (severe combined immunodeficiency [SCID]) mice. Collectively, both works provide a proof of concept that manipulating the transcriptome of tumors in favor of a pro-immunogenic phenotype can greatly improve the anti-tumor immune response and the response to ICIs.…”
Section: Epigenetic Editing By Crispr-dcas9 Can Improve Anti-tumor Host Immunitysupporting
confidence: 71%
“…As expected, the increased tumor immunogenicity via dCas9-mediated transcriptional activation of pro-immunogenic genes increased CD4 + and CD8 + T cell infiltration into the tumor, thereby improving anti-tumor immunity. The findings were also supported by Liu et al.’s 130 earlier work from 2017, where HeLa cells edited using the same dCas9-SAM system to overexpress the IFNγ gene exhibited enhanced apoptosis, inhibited proliferation, and overall reduced tumor volume when implanted in immunodeficient (severe combined immunodeficiency [SCID]) mice. Collectively, both works provide a proof of concept that manipulating the transcriptome of tumors in favor of a pro-immunogenic phenotype can greatly improve the anti-tumor immune response and the response to ICIs.…”
Section: Epigenetic Editing By Crispr-dcas9 Can Improve Anti-tumor Host Immunitysupporting
confidence: 71%
“…In the study by Wang L. et al 50 it was observed that deficiency of interferon-gamma or its receptor promotes colorectal cancer development. In the study by Liu S. et al 51 it was observed that specific expression of interferon-γ induced by synergistic activation mediator-derived (SAM) systems activates innate immunity and inhibits tumorigenesis. In the study by Razaghi A. et al 52 improved therapeutic efficacy of mammalian expressed-recombinant interferon gamma against ovarian cancer cells was observed.…”
Section: Interferon-γmentioning
confidence: 99%
“…The genetic variations in interferon-gamma (IFN-γ) and its receptor (IFN-γR) subunits are strongly associated with the risk of colorectal cancer and patient survival after diagnosis [122]. IFN-γ is a major activator of macrophages and an inducer of Class II major histocompatibility complex (MHC) molecules [123], with immune regulatory, antiviral, and antitumor properties [124,125]. Studies have shown that the deficiency of IFN-γ or its receptor promotes the development of colorectal cancer, whereas its specific expression activates innate immunity and inhibits tumorigenesis [122,124].…”
Section: Interferon-gamma (Ifn-γ)mentioning
confidence: 99%
“…IFN-γ is a major activator of macrophages and an inducer of Class II major histocompatibility complex (MHC) molecules [123], with immune regulatory, antiviral, and antitumor properties [124,125]. Studies have shown that the deficiency of IFN-γ or its receptor promotes the development of colorectal cancer, whereas its specific expression activates innate immunity and inhibits tumorigenesis [122,124]. The specific expression of IFN-γ activates innate immunity and inhibits tumorigenesis [124] However, IFN-γ signaling can also compromise antitumor immunity by inducing immune checkpoint inhibitory molecules on T and tumor cells [125].…”
Section: Interferon-gamma (Ifn-γ)mentioning
confidence: 99%